Odklady povinné školní docházky v perspektivě učitelek mateřských škol - Jana Majerčíková (Karolinum Press, 2018)
An important expectation society has of nursery schools as institutions of pre-primary education is undoubtedly the preparation of children for their admission to elementary school. This empirical study has the ambition to contribute to discussion of the issue of the postponement of the commencement of compulsory school attendance connected with this topic. Nursery school teachers with experience ranging from two to 15 years were instructed to create a professional essay during children's enrolment with the aim of sharing their opinions and experiences. The essays were assigned with the aim of revealing a number of aspects of this issue but particularly the links reflecting the various positions and effects of the main participants in the postponement − parents, children, teachers, and psychologists − and the impact of the proposed compulsory year at nursery school on the postponement. Qualitative content analysis was conducted on 25 verbal records that were from five to 10 pages in length. The analysis of the data that had been gathered showed that the key component of the postponement is the parents, who seemingly take into account the interests and needs of their children but also focus on their own interests. Teachers also perceive that there is insufficient acceptance of their own professional observations on the postponement, express disappointment with the expertise expected from counselling centres, and point out the failure to function of cooperation with primary schools.